The impact of computer-based feedback on students’ written work - El Ebyary, Khaled; Windeatt, Scott (International Journal of English Studies, 2010)
While research in second language writing suggests that instructor feedback can have a positive influence on students’ written work, the provision of such feedback on a regular basis can be problematic, especially with larger student numbers. A number of computer programs that claim to provide both automatic computer-based holistic scores and computer-based feedback (CBF) on written work are available and therefore have the potential to deal with this issue. Criterion is one such tool that claims to be able to provide automated feedback at word, sentence, paragraph and text level, but there is still a need for more research into the practical value of providing feedback on L2 writing. Quantitative and qualitative data about feedback practice was collected from 31 instructors and 549 Egyptian trainee EFL teachers using pre-treatment questionnaires, interviews and focus groups. 24 of the trainees then received computer-based feedback using Criterion on two drafts of essays submitted on each of 4 topics. Data recorded by the software suggested a positive effect on the quality of students’ second drafts and subsequent submissions, and post-treatment questionnaires, interviews and focus groups showed a positive effect on the students’ attitudes towards feedback.